Preparation and Evaluation of Topical Gel Containing Aloe Vera Exudate - Amina Al-Nima (University of Mosul, 2022)
Background:Aloe vera is known as a miracle plant belonging to the Lily (Liliaceae) family, The exudate of Aloe vera is utilized as a natural drug as it can be used for many medicinal purposes. Aims: The present work has been undertaken with the aim to prepare a topical gel containing Aloe vera exudate and to evaluate its physical properties in addition to its anti-microbialpotency in light of the orientation towards plant-based treatment for being more acceptable and preferred in the belief that they are safer with fewer side effects than synthetic ones. Aloe vera has been proved its great medicinal and cosmetic benefits. Materials and Methods: Two sets of gel formulas were prepared; the first set containing carbopol-934 (F1-F4) and the second set containing carboxymethylcellulose (F5-F10) with varied concentrations to achieve the best formula that has been selected according to various physicochemical evaluations; like homogeneity, transparency, appearance, consistency, color, odor, pH, phase separation and others. The selected formula was further subjected to in vitro study for its anti-microbial activity. Results and Discussion: There was a significant difference (p≤0.05) in physical parameters between the two sets of formulas except in pH. Results showed that (F2) containing 1.5% m/v carbopol-934 is considered the promising formula which showed better physicochemical properties and exhibited good anti-microbial activity against both (E.coli) and (Staphylococcus aureus). Conclusion and recommendations: The selected formula (F2) of Aloe vera exudate could be considered as a suitable medicinal herbal candidate for treatment of topical bacterial infections. In addition, it is recommended to use higher concentration of antioxidants to preserve the stability of the product, also it is recommended to add water soluble fragrance (perfume) for better odor.